Sproutel : how design roadmapping helped improve children's health & guide a growing company - Beckman, Sara; Kim, Euiyoung; Agogino, Alice M. (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2018)
This case aims to introduce students to the "design roadmapping" process that connects customer and user experience design with product and technology roadmapping to create an integrated plan for future growth and development. Explicit consideration of customers in the roadmapping process places customers much more centrally in the strategic planning process than has traditionally been done. The setting for the case is a seven-year-old startup company, Sproutel, that began as a college project and whose success so far has come about in part due to the use of design roadmapping.
Originally Published InBeckman, S., Kim, E., & Agogino, A. M. (2018). Sproutel: How design roadmapping helped improve children's health & guide a growing company. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sproutel -- Case studies; Strategic planning -- Case studies; New business enterprises -- Case studies; Entrepreneurship -- Case studies; Business planning -- Case studies; User interfaces (Computer systems) -- Case studies